2006
DOI: 10.1111/j.1474-9726.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of SIRT1 with cell cycle withdrawal

Abstract: SummarySir2 is an NAD + -dependent deacetylase that regulates lifespan in yeast, worms and flies. The mammalian orthologs of Sir2 include SIRT1 in humans and mice. In this study, we analyzed the level of SIRT1 in human lung fibroblasts (IMR90) and mouse embryonic fibroblasts (MEFs) from mice with normal, accelerated, and delayed aging. SIRT1 protein, but not mRNA, decreased significantly with serial cell passage in both human and murine cells. Mouse SIRT1 decreased rapidly in prematurely senescent (p44 Tg) MEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(174 citation statements)
references
References 37 publications
10
162
0
2
Order By: Relevance
“…The observation that inhibition of SIRT1 by either sirtinol or splitomicin induces senescence in H1299 (O Binda, unpublished observation;Ota et al, 2006), HUVEC (Ota et al, 2007) andMCF-7 (Ota et al, 2006) cells correlates with increased R2-mediated repression and RBP1-induced senescence, thereby providing indirect evidence suggesting that SIRT1 activity may antagonize the growth arrest phenotype caused by RBP1 family protein overexpression. A recent study, has reported that SIRT1 is gradually lost in aging cells (Sasaki et al, 2006). So, while SIRT1 levels fade away as the cells age, HDAC1-dependent transcriptional repression could be SIRT1 regulates HDAC1-dependent repression O Binda et al relieved from SIRT1 inhibition and lead to senescence, as observed with p53/PML (Langley et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…The observation that inhibition of SIRT1 by either sirtinol or splitomicin induces senescence in H1299 (O Binda, unpublished observation;Ota et al, 2006), HUVEC (Ota et al, 2007) andMCF-7 (Ota et al, 2006) cells correlates with increased R2-mediated repression and RBP1-induced senescence, thereby providing indirect evidence suggesting that SIRT1 activity may antagonize the growth arrest phenotype caused by RBP1 family protein overexpression. A recent study, has reported that SIRT1 is gradually lost in aging cells (Sasaki et al, 2006). So, while SIRT1 levels fade away as the cells age, HDAC1-dependent transcriptional repression could be SIRT1 regulates HDAC1-dependent repression O Binda et al relieved from SIRT1 inhibition and lead to senescence, as observed with p53/PML (Langley et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…1C, lower right). In addition to morphological changes and SA-b-gal positivity, the histone deacetylase sirtuin-1 (SIRT1), also a marker of cellular senescence (37), was also decreased in L-PDMCs from different donors (Fig. 1D, E).…”
Section: Pdmcs Become Senescent With Prolonged In Vitro Culturementioning
confidence: 99%
“…Significantly, a decreased level of expression of the closest mammalian ortholog of Sir2, SirT1, correlates with apparent premature aging of mice with increased activity of p53 family members [24]. Moreover, in aging wild type mice, SirT1 protein level decreases with age in mitotic tissues [25]. Thus, the ability of Sir2-like proteins to regulate aging appears to be conserved through evolution.…”
Section: Aging Is Associated With Epigenetic Changes From Yeast To Hmentioning
confidence: 99%